2004
DOI: 10.1159/000079807
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Immunosuppressive Regimens on Antigen-Presenting Blood Cells in Kidney Transplant Patients

Abstract: Background: Alloantigen-specific and unspecific immune processes contribute to chronic renal graft dysfunction. Despite ‘optimized immunosuppressive therapy’ (IS), the role of chronic cell activation still remains open. Methods: 69 kidney transplant recipients (NTX) were assessed for monocyte surface antigens CD14 (LPS receptor) and CD16 (Fc-γ-III receptor) by flow cytometry including the percentage amount of the proinflammatory CD14+CD16+ subset. 14 non-dialysis patients with chronic renal failure (CRF) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Recent preliminary data showed a partial reduction in CD16+ monocyte count in a group of TX recipients (25). Our report confirms these data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent preliminary data showed a partial reduction in CD16+ monocyte count in a group of TX recipients (25). Our report confirms these data.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, patients suffering from end-stage renal disease have higher numbers of proinflammatory CD14+CD16+ monocytes compared to healthy controls (8)(9)(10)(11)(12). This shift in monocyte subpopulations may contribute to the accelerated atherosclerosis in dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our results, the presence of an increased percentage of intermediate and non-classical monocytes in end-stage kidney disease patients undergoing dialysis has been reported [25], [26], [28], [32], [33] Scherberich et al found an increase in the monocyte subset co-expressing CD14 with CD16 in patients with chronic renal failure [27]. The authors investigated the effect of different immunosuppressive regimens on the frequency of intermediate and non-classical monocytes.…”
Section: Discussionsupporting
confidence: 90%
“…We did not evaluate the clinical significance of this reduced HLA-DR expression but, this might be one of the reasons why organ transplant recipients are 'immunocompromised', transforming an otherwise simple viral infection into a dangerous, severe complication. Similarly, Scherberich et al [11] also found a downregulation in monocyte surface antigen CD14 (lipopolysaccharide receptor) and CD16 (Fc-III receptor) by flow cytometry in transplant recipients.…”
Section: Discussionmentioning
confidence: 77%